Trimming-Less 0.2-V, 3.2-pW Voltage Reference Based on Corner-Aware Replica Combination with 1.6% Process Sensitivity, 1.4-mV Accuracy across PVT and Wafers - Fassio, Luigi (IEEE, 2021)
IEEE ESSCIRC 2021